How high velocity organizations get ahead and stay ahead - Spear, Steven J. (Henry Stewart Talks, 2012)
G-A-P-S, Making giant leaps, Moon mission, Mercury, Gemini, Apollo, Explorer, Stumbling to catastrophe, Catastrophe: whose fault?, Symmetry of success and failure, See problems, Solve problems, Share discoveries, Lead improvement
Reviewed at 2020/02/27